Job satisfaction and employee retention by public and private IT organizations - Steil, Andrea Valéria; Bello, Janine da Silva Alves; Cuffa, Denise de; Freitas, Aline Ferreira de (Revista de Administração da UFSM, 2022)
Purpose: Examine the relationship between global job satisfaction, as well as the dimensions of satisfaction (satisfaction with the nature of work, colleagues, leadership, salary and promotions), with the retention of IT professionals in public and private IT institutions. Design/methodology/approach: Data were collected from 252 professionals from IT institutions (139 from public institutions and 113 from private institutions) located in the state of Santa Catarina, Brazil. Data were collected using a survey and analyzed via Spearman’s rank correlation coefficient. Findings: There was no positive correlation between the measures of global satisfaction nor the satisfaction with the nature of work, colleagues, leadership and promotions with retention of professionals. Only the satisfaction with salary showed positive correlation with retention of IT professionals in public and private IT institutions. Practical implications: These results set the ground for the establishment of policies aimed at retaining IT professionals, especially related to salary. Originality/value: This study investigates not only the global measurement of satisfaction but also its dimensions. The study shows for the first time that global job satisfaction isn’t retaining professionals in public not private IT organizations, and that retention strategies need to focus especially on salary satisfaction of these professionals.